Hubungan Pengetahuan Dengan Motivasi Menggunakan Jaminan Kesehatan Nasional (JKN) Di Puskesmas Panarung - Rizka Ovany; Hermanto Hermanto; Titus Suprianto (Jurnal Surya Medika (JSM), 2020)
The National Health Insurance (JKN) is carried out with a social health insurance mechanism that is mandatory to meet the basic health needs of the community that pays contributions or is paid by the Government. This is not well understood by many families so there are still families who have not used national health insurance on the grounds that they rarely get sick and do not use it when they seek treatment. This study aims to see the relationship of knowledge with motivation in using JKN. This type of correlation study with a purposive sampling technique, data collection using questionnaires in the form of closed statements as many as 11 items about national health insurance knowledge (JKN), and as many as 15 items of questions. Motivational measurements were given to 35 respondents. The statistical test uses the Rho Spearmen Test (Rank). From 35 respondents, there were 22 respondents (62.9%) lacking knowledge with 16 respondents (45.7%) moderate motivation and 6 respondents (17.1%) strong motivation while 9 respondents had sufficient knowledge level (9 respondents) 25.7%) with the strong motivation of 6 respondents (17.1%) and a moderate motivation of 3 respondents (8.6%) while respondents who have a good level of knowledge amounted to 4 respondents (11.4%) with the strong motivation of 4 respondents (11.4%) and moderate motivation (0%). With the analysis test resultsusing the Rho Spearmen (Rank obtained P-Value 0.002 (0.002 <0.05).